The constitution: views from homoeopathy and psychiatry - Gaylord, SA; Davidson, J (British Homeopathic Journal, 1998)
The notion that individuals differ in their physical and psychical makeup, and that these differences predispose them to various illnesses, is found throughout medical history in various healing traditions. In this paper, the authors address the use of the concept of constitution and constitutional type in homoeopathy, as well as in psychiatry, and describe an approach toward validating the existence of such types in the population.